Análise do processo de adoção/construção de conhecimentos pelos agricultores familiares do assentamento banco da terra, Nova Xavantina - MT - Moraes, Murilo Didonet de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Family farming has great importance inside the Brazilian agricultural scenario, but both the survival as the strengthening of this category of farmers are closely related to knowledge applied to the production process. The present work aims to analyze how occurs the adoption/construction process of knowledge by family farmers. Although the research involved collecting quantitative data, gave greater emphasis to qualitative type investigation, which was conducted in the settlement Banco da Terra in Nova Xavantina-MT. The methodology used in the study was composed of two stages: the first 24 questionnaires were applied (41.7% of households), with open and closed questions, with the goal of meeting the socioeconomic, productive and cultural characteristics of the settlers. The second stage of the research consisted of applying semi-structured interviews to settlers and the entities responsible for spreading knowledge to this public, in order to identify the ways of interaction between both the positive and negative points of this process. The results demonstrate that the socioeconomic characteristics of the farmers point to an environment little conducive to adoption/construction of knowledge, due to advanced age, low values of monetary income, high rate of leased lots, restricted labour availability and low grade schooling. On the other hand, it was observed that in farms developed in the batches, the self-knowledge and experience appear as the underpinning of all actions used by farmers. Furthermore, the factors related to the economic and technical aspects appeared with a smaller percentage, thus demonstrating a minor influence on the decision-making process of farmers than aspects closer to psychosocial and cultural characteristics, suggesting that the more geared knowledge to the longings and experiences of farmers will be adopted/constructed more easily. In this way, the most important result ...

A agricultura familiar tem grande importância dentro do cenário agrícola brasileiro, porém tanto a sobrevivência como o fortalecimento desta categoria de agricultores estão estritamente relacionados ao conhecimento aplicado ao processo de produção. O presente trabalho tem como objetivo analisar como ocorre o processo de adoção/construção de conhecimentos pelos agricultores familiares. Embora a pesquisa envolva a coleta de dados quantitativos, deu-se maior ênfase à investigação do tipo qualitativa, a qual foi realizada no Assentamento Banco da Terra em Nova Xavantina - MT. A metodologia empregada na pesquisa foi composta por duas etapas: na primeira foram aplicados 24 questionários (41,7% das famílias), com perguntas abertas e fechadas, com o objetivo de conhecer as características socioeconômicas, produtivas e culturais dos assentados. A segunda etapa da pesquisa constou da aplicação de entrevistas semiestruturadas aos assentados e às entidades responsáveis por difundir o conhecimento a este público, com o intuito de identificar as formas de interação entre ambos, os pontos positivos e negativos desse processo. Os resultados demonstram que as características socioeconômicas dos agricultores apontam para um ambiente pouco propício à adoção/construção de conhecimentos, devido à idade avançada, baixos valores da renda monetária, alto índice de lotes arrendados, disponibilidade de mão de obra restrita e baixo grau escolaridade. Por outro lado, observou-se que nas explorações desenvolvidas nos lotes, o conhecimento próprio e a experiência aparecem como balizadores de todas as ações utilizadas pelos agricultores. Além disso, os fatores ligados aos aspectos econômicos e técnicos apareceram com uma menor porcentagem, demonstrando assim uma menor influência na tomada de decisão dos agricultores do que os aspectos mais próximos às características psicossociais e ...
Keywords: Agricultura familiar; Teoria do conhecimento; Assentamentos rurais; Family farms